PENGARUH TINGKAT PENGANGGURAN TERBUKA, KEMISKINAN DAN KETIMPANGAN PENDAPATAN TERHADAP KRIMINALITAS DI PROVINSI ACEH - Syafira, Syarifah; Mawarni, Hasri (LPPM UNIMAL, 2024)
This research aims to determine the influence of open unemployment, poverty and income inequality on crime in Aceh Province. The data used in this research is secondary data in the form of a time series for 1999-2023 obtained from the Aceh Central Statistics Agency. The data analysis method uses multiple linear regression. The research results show that the level of open unemployment and income inequality have a positive and insignificant effect on crime in Aceh Province. Meanwhile, poverty has a negative and significant effect on crime in Aceh Province. Simultaneously, the level of open unemployment, poverty and income inequality have a significant effect on crime in Aceh Province.